Skeletal Anomalies of Juvenile Smooth Newts - Lissotriton vulgaris - Perekhrest, E V; Trofimov, A G; Berzin, D L (KnE Life Sciences, 2018)
An article contains first data on internal skeletal anomalies of smooth newt juveniles. The material was collected on the territory of urban agglomeration of Yekaterinburg. We found 16 variants of anomalies. An increase of general frequency of deviations along urbanization gradient were mentioned. The differences and specificity of the populations spectra are related with the profiling of the juveniles definitive morphology by environmental specifics.